Fuzzy-ball fluid self-selective profile control for enhanced oil recovery in heterogeneous reservoirs: The techniques and the mechanisms. (1st September 2020) - Wei, Panfeng; Zheng, Lihui; Yang, Mingzheng; Wang, Chao; Chang, Qifan; Zhang, Wang
Highlight: Proposed A new fluid technology for EOR in heterogeneous reservoirs. The fluid can actively plug high-permeability areas to divert flooding agents. The surfactant and polymer components in the fluid can enhance overall EOR effects. The fluid system contains no solid phase, which minimizes formation damage. Abstract: Conventional water flooding and polymer flooding are common approaches to improve oil recovery. However, flooding agents injected into heterogeneous reservoirs preferentially enter the seepage channels in high-permeability zones. As a result, it is difficult to displace the hydrocarbons in low-permeability areas. Therefore, using the agents with selective plugging capability to block the high-permeability channels and promote the subsequent displacement in the low-permeability area has become a potentially preferable solution for enhanced oil recovery (EOR) in heterogeneous reservoirs. In this study, the techniques and mechanisms of the novel fuzzy-ball fluid for enhancing oil recovery in heterogeneous reservoirs are discussed. Laboratory tests were conducted using 45 mm × 45 mm × 300 mm artificial cores with permeability ranging from 200 to 1200 mD to simulate the formation channels. Two cores with different permeabilities were connected in parallel to simulate the heterogeneous formations. The oil displacement performance of fuzzy-ball fluid was compared with that of polymer and surfactant fluids. Flooding the cores with fuzzy-ball fluid could significantly increase the oil recovery rate of the low-permeability cores. Field tests were conducted in two polymer injection wells located in a heterogeneous conglomerate reservoir in Karamay Oilfield, China. After fuzzy-ball fluid flooding, the average daily liquid production rate decreased, the average daily oil production rate increased and the overall water content decreased. There was a significant improvement in oil displacement effect in low-permeability areas.